Sarcoidosis. A review of diagnosis, clinical features and treatment - Madej, Aleksandra; Senat, Hanna; Grabowska, Patrycja; Bolla, Patrycja; Senat, Aleksandra; Marczyńska, Zuzanna (Journal of Education, Health and Sport, 2024)
Introduction: Sarcoidosis is a progressive chronic multisystemic inflammatory disease of unclear pathogenesis, which presents with noncaseating granulomas and is complicated to diagnose due to the variable clinical presentation of patients. Sarcoidosis may attack any organ, but especially the pulmonary, cutaneous, lymphatic, ocular, hepatic and splenic systems. The most frequent presentations are prolonged cough, rash, visual problems, peripheral lymphadenopathy, tiredness, and occasional abnormality of the chest X-ray. The diagnostic evaluation of sarcoidosis is difficult and often involves a combined effort of clinical data and appropriate imaging modalities. Purpose: The purpose of this article is to review the available literature on the epidemiology, clinical manifestations and management of patients with sarcoidosis Materials and method: The available literature in PubMed was reviewed to write the article, using the keywords ,,sarcoidosis”, ,,cardiac sarcoidosis”, ,,pulmonary sarcoidosis” and ,,cutaneous sarcoidosis”. Conclusion: Sarcoidosis is associated with a significant increase in patient mortality, as well as decreased quality of life and physical disability. Efforts to accurately predict disease progression allow for more comprehensive and personalized patient care. As a life threatening disease, sarcoidosis needs to be diagnosed early and treated appropriately.